DAYA SAING UNGGUL MELALUI LOYALITAS DAN MARKETING 3.0 SERTA DIMENSI INOVASI PADA PROGRAM PASCASARJANADI JAKARTA - Susilo, Wilhelmus Hary (KINERJA, 2015)
A concept is developed from the marketing 3.0 towards achieving the competitiveness higher education in Jakarta. This research conducts the hybrid models of marketing 3.0 on model structural equation. Thesample used in this study are 105 post graduate students at 3 institutions.The findings of this research suggests hybrid models marginal fit with the chi-square = 420.7, GFI = .73 and CFI = .97. Hypothesis that confirms pertains; influence communitization of the decision by the purchase (t = 3.69), influence building character of competitiveness (t = 5.72), communitization influence on competitiveness (t = 2.80 , the decision the purchase of loyalty (t = 2.80) and marketing 3.0 any impact, the purchase, and loyalty simultaneously on competitiveness institutions with R2 = .98 .Then the dimensions; encouragement and action purchase of purchase variable decision that deals with dimensions; innovation, purchase repeated, resistant to competitors, recommended and buy other line of the loyalty, with an r ( er )value = .99 .Keywords: competitiveness, loyalty, marketing 3.0, innovations